2018
DOI: 10.1016/j.powtec.2018.01.057
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the photocatalytic activity of TiO 2 nanoparticles encapsulated by chitosan through a spray-drying method with potential for use in sunblocking applications

Abstract: K. (2018). Suppression of the photocatalytic activity of TiO2 nanoparticles encapsulated by chitosan through a spray-drying method with potential for use in sunblocking applications. Powder Technology, 329 252-259. AbstractSolar exposure, in particular to UVA and UVB radiation, is a major carcinogen through direct DNA damage and the production of reactive oxygen species (ROS). Inorganic UV filters present in sunscreening agents, such as titanium dioxide (TiO 2 ), are commonly employed for protection however, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Furthermore, Morlando et al reported that the thermostability of nanocomposites could be reduced through the addition of TiO 2 NPs. This is probably due to the thermal conductivity of the ceramic TiO 2 NPs, leading to an equal distribution of heat to the samples [54].…”
Section: Thermal Gravimetric Analysismentioning
confidence: 99%
“…Furthermore, Morlando et al reported that the thermostability of nanocomposites could be reduced through the addition of TiO 2 NPs. This is probably due to the thermal conductivity of the ceramic TiO 2 NPs, leading to an equal distribution of heat to the samples [54].…”
Section: Thermal Gravimetric Analysismentioning
confidence: 99%
“…ZnO, as one of the inorganic UV-absorbers has been used to formulate UV shielding materials such as sunscreens. Surface modifications such as silica coating [13], impurity doping [14,15], polymer stabilization [16,17], capping agents [18] and metal oxides hetero-composites [1,4,19] have been implemented to tune the photo response properties of ZnO for possible application in reducing the effects of UV absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic particles are not easily dispersed in creams, which greatly limits their application in skincare products. Morlando et al (2018) utilized the antioxidant properties of chitosan to capture the free radicals generated by the photocatalytic activity of TiO2. However, the prepared chitosan/TiO2 nanocomposite particles had weak UV absorption capacity.…”
Section: Introductionmentioning
confidence: 99%